2020
DOI: 10.4028/www.scientific.net/kem.859.145
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, and Microbiological Stability of <i>Mucuna pruriens</i> Effervescent Powders and Suspension

Abstract: Mucuna pruriens is a tropical leguminous plant containing L-dopa which is the main active ingredient for Parkinson’s disease therapy. The objective of this study was to investigate the physical, chemical, and microbiological stability of M. pruriens seed extract effervescent powders and suspension. The effervescent powders and suspension were prepared using freeze dried M. pruriens seed extract and were stored at 4 °C, 30 °C, and 45 °C. Physical stability was evaluated by observing appearance and determining r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Chromatographic separation was carried out using C 18 column (Inertsil ® ODS-3, 250 mm × 4.6 mm, i.d. 5 µm) with isocratic elution and UV detection at 283 nm [ 17 ]. The mobile phase consisted of a 0.025 M ortho-phosphoric acid buffer pH 2.5 and pumped at a flow rate of 1.0 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Chromatographic separation was carried out using C 18 column (Inertsil ® ODS-3, 250 mm × 4.6 mm, i.d. 5 µm) with isocratic elution and UV detection at 283 nm [ 17 ]. The mobile phase consisted of a 0.025 M ortho-phosphoric acid buffer pH 2.5 and pumped at a flow rate of 1.0 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, at GI temperature, M. pruriens extract jelly may transform to sol and help release the L-dopa. The pH of the jelly containing M. pruriens extract was mildly acidic, 4.77±0.02, which could help maintain the chemical stability of L-dopa in the product [2]. The physical stability study showed that M. pruriens extract jelly was more stable when stored at 4 °C compared with 30 °C.…”
Section: Physical Characteristics and Stability Of M Pruriens Extract...mentioning
confidence: 99%